2018
DOI: 10.14744/nci.2018.82957
|View full text |Cite
|
Sign up to set email alerts
|

The Hepatoprotective Effect of Aloe Vera on Ischemia-Reperfusion Injury in Rats

Abstract: OBJECTIVE:Aloe vera is known for its antioxidant properties. In this experimental study, we aimed to investigate the efficacy of Aloe vera in ischemia-reperfusion (I/R) liver injury in rats.METHODS:Male Wistar Albino rats were divided into three groups, where the sham group (n=7) underwent no medication or surgical procedures, the I/R group (n=7) was the control group that received 45 minutes of applied abdominal aorta ischemia and rats were sacrificed 24 hours after reperfusion, and the I/R+AV group (n=7) was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 27 publications
1
14
0
Order By: Relevance
“…Our study revealed that SOD-1, SOD-2, GPX and CAT levels were decreased following ROSC in Group II compared with Group I. The levels of these antioxidant enzymes are reduced following I/R, which causes cell damage and death due to the consumption of endogenous antioxidants as a result of ROS release ( 52 ).…”
Section: Discussionmentioning
confidence: 85%
“…Our study revealed that SOD-1, SOD-2, GPX and CAT levels were decreased following ROSC in Group II compared with Group I. The levels of these antioxidant enzymes are reduced following I/R, which causes cell damage and death due to the consumption of endogenous antioxidants as a result of ROS release ( 52 ).…”
Section: Discussionmentioning
confidence: 85%
“…SOD activity has been shown to decrease in the liver, lung, and ileum in rat models of I/R injury [ 44 - 46 ]. SOD levels decrease after I/R [ 6 ], and the consumption of SODs due to ROS overproduction causes cell damage or death [ 12 ]. We evaluated whether hypothermia treatment was associated with an imbalance antioxidants in the rat liver by examining the expression of antioxidant enzymes (SOD1 and SOD2) by immunohistochemistry and found that immunoreactivities of SOD1 and SOD2 were much higher in the HT/ACA group than in the NT/ACA group.…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with these findings, hypothermic treatment has been reported to offer protection by enhancing the endogenous defense system and increasing the expression of antioxidant enzymes [ 47 ]. In addition, consumption of endogenous antioxidants due to the release of ROS causes apoptotic and necrotic cell death [ 12 ] and hypothermia reduces apoptosis [ 48 ] and necrotic damage at the cellular level by reducing ROS accumulation [ 49 ]. Increased immunoreactivities of liver SOD1 and SOD2 in the HT/ACA group suggest that hypothermia treatment protects against liver inflammation by increasing the expression of antioxidant enzymes that then scavenge oxygen free radicals after I/R.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Determination of serum oxidative stress index. As previously described (22,23), the content of malondialdehyde (MDA) was detected by thiobarbituric acid colorimetry; the content of GSH and the activity of oxide dismutase (SOD) were determined by chemical methods. The kits for MDA (cat.…”
Section: Methodsmentioning
confidence: 99%